Synthesis of geopolymer from rice husk ash for biodiesel production of Calophyllum inophyllum seed oil - Saputra, E.; Nugraha, M.; Helwani, Z.; Olivia, M.; Wang, Shaobin (Institute of Physics Publishing Ltd., 2018)
In this work, geopolymer was prepared from rice husk ash (RHA) made into sodium silicate then synthesized by reacting metakaolin, NaOH, and water. The catalyst was characterized using Scanning Electron Microscopy (SEM), Energy-dispersive X-Ray analysis (EDX), Brunaeur Emmet Teller (BET), and basic strength. Then, the catalyst used for transesterification of Calophyllum inophyllum seed oil in order to produce biodiesel. The variation of process variables conducted to assess the effect on the yield of biodiesel. The highest yield obtained 87.68% biodiesel with alkyl ester content 99.29%, density 866 kg/m3, viscosity 4.13 mm2/s, the acid number of 0.42 mg-KOH/g biodiesel and the flash point 140 °C. Generally, variations of %w/w catalyst provides a dominant influence on the yield response of biodiesel. The physicochemical properties of the produced biodiesel comply with ASTM standard specifications.